Periostitis ossificans in a 10-year-old child - Camilla Marcelino; Maria Dalla Costa; Alexandre Roberto Heck; Mary Aparecida Pereira Heck; Fabian Calixto Fraiz (Wolters Kluwer Medknow Publications, 2020)
Periostitis ossificans (PO) is a type of osteomyelitis stemming from an odontogenic infection, generally found in children and adolescents, and often leads to the loss of the involved tooth. This case presents a less invasive alternative for the treatment of PO. A 10-year-old patient presented with an asymmetrical increase in the left side of the mandible. Tooth 36 exhibited pulp necrosis and incomplete root formation. Radiographically, the bone in the region had the appearance of the layers of an onion. Computed tomography indicated periosteal bone proliferation in the region of the ramus and angle of the mandible adjacent to the vestibular cortical bone. Therapy involved root canal preparation and intracanal medication with calcium hydroxide in tooth 36. Complete remission of the condition occurred within 14 months. In conclusion, endodontic intervention is a less invasive alternative and should be considered to minimize the negative impact of tooth loss in children.